1982
DOI: 10.3758/bf03327019
|View full text |Cite
|
Sign up to set email alerts
|

Strain of foster mother determines long-term effects of early handling: Evidence for maternal mediation

Abstract: Inbred A/J mice were raised from birth by foster mothers of either the AlJ or C57BII6J strain. Some litters of each maternal rearing condition were handled during the preweaning period, whereas others were not. In adulthood, the behavior of females in the open field as well as the plasma corticosterone levels of males following both no disturbance and placement in a novel environment were examined. Defecation in the open field was found to be greater in handled than in nonhandled subjects, but only for those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In recent studies, we have found evidence for the idea that the effects of handling on either endocrine (Liu et al 1997) or behavioral/emotional (Caldji et al 1998) responses to stress are mediated by handlinginduced changes in maternal behavior (Smotherman and Bell 1980;Hennessy et al 1982). Mothers of handled pups exhibit increased licking/grooming and arched-back nursing (Lee and Williams 1975;Liu et al 1997;Caldji et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, we have found evidence for the idea that the effects of handling on either endocrine (Liu et al 1997) or behavioral/emotional (Caldji et al 1998) responses to stress are mediated by handlinginduced changes in maternal behavior (Smotherman and Bell 1980;Hennessy et al 1982). Mothers of handled pups exhibit increased licking/grooming and arched-back nursing (Lee and Williams 1975;Liu et al 1997;Caldji et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While these results are very preliminary (e.g., cortisol responses were not measured following a second separation; only one time point was assessed), they suggest that reduced glucocorticoid suppression of proinflammatory processes during subsequent separations may help account for the more-rapid febrile response and increased passive behavior. In rats and mice, lasting effects of early separation on glucocorticoid levels and other measures often appear to be mediated by the treatment of the pups by the mother upon return to the home cage [e.g.,30,38]. In the precocial guinea pig, by contrast, active maternal care rarely is observed beyond the first week postpartum [35], even following separation and reunion [25].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the nature of these factors remains to be elucidated. An obvious but unlikely possibility is suggested by evidence indicating that the effects of early postnatal handling on behavioural and neuroendocrine responses to stress are mediated by changes in maternal behaviour (Smotherman & Bell, 1980; Hennessy et al ., 1982; Liu et al ., 1997; Caldji et al ., 1998). Indeed, mothers respond to H pups with increased licking/grooming behaviour and arched‐back nursing (Lee & Williams, 1975; Liu et al ., 1997; Caldji et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%